Infestation of Apis mellifera L. bee colonies by a mite of the genus Tropilaelaps spp. in the conditions of Russia - A. Z. Brandorf; L. Xing’an; N. Qingsheng (Аграрная наука Евро-Северо-Востока, 2025)
In recent years, there has been a massive loss of bee colonies in the Russian Federation, which is caused, among other things, by the appearance of a new disease, Tropilopsis. Previously, it was believed that a mite of the genus Tropilaelaps could not infect bee colonies in Eurasia, but in 2021, an infestation of bee colonies Tropilelaps mercedesae was discovered in the Krasnodar Region of the Russian Federation. The aim of the research is to study the features of the infestation of bee colonies by a mite of the genus Tropilelaps in Russia. In 2022–2024 studies were conducted in the Krasnodar Region, the morphometric characteristics of ticks were studied, and a comparison was made with mites from other populations: the Republics of Dagestan and Abkhazia, Georgia, China, and India (n = 200). A comparative analysis of diagnostic methods was carried out with the identification of reliable (n = 10). For comparative diagnosis, the following methods were used: visual, alcohol flushing, brood uncapping, natural mortality. It was revealed that more than 35 % of the infection rate is recorded in bee colonies from July to October, no mite was detected in the brood from February to April, and the number of mites in one cell varies throughout the year. An effective way to diagnose the infestation of bee colonies by a tick has been identified – uncapping of sealed brood, which makes it possible to diagnose the lesion of bee colonies at an early stage. The visual assessment method makes it possible to diagnose the disease when the brood is affected by more than 30 %. Mites from the Krasnodar Region differ in the size of the dorsal shield from other populations studied, their length-to-width ratio is on average less than 10 % compared with mites from Georgia, the Republic of Abkhazia, China and India. In order to identify the formation of individual populations adapted to certain natural and climatic conditions the further study of the Tropilelaps mercedesae mite is necessary.